2011
DOI: 10.1016/j.jpurol.2011.02.026
|View full text |Cite
|
Sign up to set email alerts
|

Quality of life in children with vesicoureteral reflux as perceived by children and parents

Abstract: In terms of HRQoL, VUR is a benign clinical entity and neither antibiotic use nor UR is associated with lower HRQoL. Disease-specific quality of life surveys are needed to accurately evaluate patient and parent satisfaction in the management of VUR.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 21 publications
0
8
1
Order By: Relevance
“…Based on the chronicity of the therapy and management of VUR, a potential impact on HRQoL can be anticipated, but the literature on HRQoL in paediatric VUR is still sparse. Previous studies have reported diverse and somewhat contradictory results, both regarding the families' HRQoL [66][67][68] as well as the parents' satisfaction and preferences [69][70][71][72][73].…”
Section: Vur and Quality Of Lifementioning
confidence: 99%
“…Based on the chronicity of the therapy and management of VUR, a potential impact on HRQoL can be anticipated, but the literature on HRQoL in paediatric VUR is still sparse. Previous studies have reported diverse and somewhat contradictory results, both regarding the families' HRQoL [66][67][68] as well as the parents' satisfaction and preferences [69][70][71][72][73].…”
Section: Vur and Quality Of Lifementioning
confidence: 99%
“…In contradiction to the above, Yao et al [5] found no major significant differences in QOL scores between patients with and without VUR and concluded that VUR per se acted as a benign entity, without affecting quality of life of children affected. They, however, stated that few patients had lower QOL because they were taking antibiotics and undergoing surveillance tests, such as radionuclide cystogram (RNC) or MCU.…”
Section: Discussionmentioning
confidence: 94%
“…[45] Due to the overwhelming advantages most parents primarily select endoscopic therapy,[3] but very less is yet known about the subjective impact of this minimally invasive treatment on children's well being in terms of their quality of life. [45] Generally, HRQOL is defined as “the extent to which one's usual or expected physical, emotional, and social well being are affected by a medical condition or its treatment”. [4]…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations